The Culture of Luxury at the service of humanity (Revista de Ensino em Artes, Moda e Design, 2021)
We have witnessed a stagnation of the culture of luxury in the throughout 2020, since the production in China and Italy have been completely compromised. Thus, we can observe in this period some interesting and aligned initiatives from big trademarks and merged corporations to the global moment. Given this scenario, we see how much the luxury market is entrenched in our culture. Certainly, even though luxury is associated with some uselessness, at a time of global crisis, this market shows how it can be useful. Besides that, as we know, luxury is linked to the idea of eternity and dream, vectors that are intensified in times of uncertainty. To understand the meaning vectors triggered by this sector, especially in fashion’s universe, and how it can be fundamental to humanity – even if it’s related to superfluous – we resort to some author’s collaboration such as Renato Ortiz (2019), Gilles Lipovetsky e Eliette Roux (2005) and Claudio Diniz (2012). Therefore, we highlight three reflective moments to be prioritized: a) an approach about the luxury imaginary, its values and its relation with the contemporaneous ways of living; b) the democratization of what is apparently restrictive; and c) the proliferation of luxury in Brazil, emphasizing above all the indissociability of luxury in human culture.
Keywords: Culture; Luxury; Fashion; Beauty